How did the first pandemic COVID wave affect acute myocardial infarction hospital assistance?. (14th October 2021) - Pacheco, A; Carvalho, D; Carvalho, P; Ferraz, L; Briosa, A; Bem Haja, P; Bastos, M
Abstract:  : There is a general notion that the COVID pandemic has made access to adequate health care difficult. A retrospective study looked at patients with acute myocardial infarction (AMI) admitted to a hospital, including the time between admission and diagnosis, the time until treatment, and the delay in transferring to a hospital with a catheterization laboratory in the case of ST-Elevation Myocardial Infarction (STEMI).The period analysed was March to July 2019 and March to July 2020 (first Covid pandemic wave). 197 patients, 101 in 2019 (SCA19) and 96 in 2020 (SCAcov), 142 males (72%) mean age 67.3±12.6. It was observed in 2019 29 STEMI and 72 acute myocardial infarct without ST elevation (NSTEMI) na 2020 36 STEMI and 60 NSTEMI, this proportions didn't achieve statistical meaning χ 2 (1)=1.719, p=0.226. When compared SCA19 versus SCAcov there were no differences between groups in relation to demographic data. The clinical presentation (none, hemodynamic instability, refractory pain, arrhythmia, mechanic complication, acute heart failure) not varied between groups χ 2 (6)=3.42, p=0.755. When analysed, between SCA19 and SCAcov, there were no significant time difference between the admission and the electrocardiogram execution (MSCA19 = 44.78; MSCAcov = 56.84; Tweich (132.66) = −0.73, p=0.476 g Hedge = 0.71, between time of admission and time of diagnosis MSCA19 = 264.84; MSCAcov = 254.2; Tweich (188.81) = −0.34, p=0.731 g Hedge = 0.05, and the duration of hospitalization MSCA19 = 5.90; MSCAcov = 5.78 U=9400, Z=−0.263, p<0.792. Conclusion: In COVID times even with the all restrictions and contingencies lived in hospitals our results pointed to no significant changes in the variables analysed. Interestingly, in spite of no significant difference, a slightly more delay in ECG execution, higher prevalence of STEMI but a short time of diagnosis were observed. FUNDunding Acknowledgement: Type of funding sources: None.